1999
DOI: 10.1073/pnas.96.21.12004
|View full text |Cite
|
Sign up to set email alerts
|

Race-specific HIV-1 disease-modifying effects associated with CCR5 haplotypes

Abstract: Genetic variation in CC chemokine receptor 5 (CCR5), the major HIV-1 coreceptor, has been shown to influence HIV-1 transmission and disease progression. However, it is generally assumed that the same CCR5 genotype (or haplotype) has similar phenotypic effects in different populations. To test this assumption, we used an evolutionary-based classification of CCR5 haplotypes to determine their associated HIV-1 disease-modifying effects in a large wellcharacterized racially mixed cohort of HIV-1-seropositive indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
332
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(368 citation statements)
references
References 23 publications
34
332
2
Order By: Relevance
“…Of additional interest, HIV ϩ persons with a Ϫ2459A͞A ϩ ORF⌬32͞wt diplotype demonstrated the lowest levels of plasma viremia. Furthermore, our data linking ex vivo R5 HIV susceptibility to CCR5 genotype are also consistent with additional cohort data correlating CCR5 genotype and HIV disease progression as reported by two other studies (33,35). Thus, our current ex vivo infection findings with LCs provide a plausible biologic explanation for observed epidemiologic data obtained from large cohorts of individuals regarding host genetic susceptibility to HIV infection.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Of additional interest, HIV ϩ persons with a Ϫ2459A͞A ϩ ORF⌬32͞wt diplotype demonstrated the lowest levels of plasma viremia. Furthermore, our data linking ex vivo R5 HIV susceptibility to CCR5 genotype are also consistent with additional cohort data correlating CCR5 genotype and HIV disease progression as reported by two other studies (33,35). Thus, our current ex vivo infection findings with LCs provide a plausible biologic explanation for observed epidemiologic data obtained from large cohorts of individuals regarding host genetic susceptibility to HIV infection.…”
Section: Discussionsupporting
confidence: 79%
“…4B). As four different haplotypes have been identified that contain the Ϫ2459G allele (haplotypes A-D) and three different haplotypes have been identified that contain the Ϫ2459A allele [haplotypes E, F1, and G1; excludes haplotypes containing CCR264I (F2) and ORF⌬32 (G2) (33)], it is important to note that no single Ϫ2459G haplotype was consistently associated with a low percentage of p24 ϩ LCs and no single Ϫ2459A haplotype was consistently associated with a high percentage of p24 ϩ LCs. Although significant differences in HIV infection levels in LCs among individuals who were homozygous for the wild-type ORF with either Ϫ2459A͞A,Ϫ2459A͞G, or Ϫ2459G͞G promoter genotypes were not detected, LCs isolated from Ϫ2459G͞G individuals tended to be less susceptible to HI V than LCs isolated from Ϫ2459A͞A individuals (Ϫ2459G͞G, n ϭ 13; Ϫ2459A͞A, n ϭ 15; Mann-Whitney U test, P ϭ 0.093; Fig.…”
Section: Compound Ccr5 Polymorphisms Influence R5 Hiv Infection Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown correlations between disease progression and the CCR2-64 I/V amino acid substitution and between CCR5 promoter haplotype/haplotype combinations (diplotype) [10,19,[23][24][25][26][27][28]. We were unable to demonstrate any relationship between these diplotypes and the in vitro phenotype; however, these additional analyses may have been limited by the small numbers of individuals in the diplotype in vitro phenotype categories observed in this study.…”
Section: Resultscontrasting
confidence: 47%
“…The errors introduced by this assumption should be very small, as RH index differences between racial groups are generally small (see Table 1 in Winkler et al). 12 However, it was recently shown that the RH indices of the haplotypes containing newly identified polymorphisms in the promoter region of CCR5 [19][20][21] are higher in African Americans than they are in European Americans. 19 Therefore, the RH index in African populations in this study is likely to be underestimated and our conclusion of high RH in Africa still stands.…”
Section: Resultsmentioning
confidence: 99%